Długie życie seriali z lat dziewięćdziesiątych XX wieku w najnowszej kulturze popularnej = The long life of series from the nineties of the twentieth century in recent popular culture - Piechota, Dariusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article is devoted to analysing and interpreting popular soap operas from the 1990s, arousing nostalgia for a carefree childhood. We learn about the rich Americans' lifestyle and older brothers' and sisters' idols.
Keywords: "Dynastia"; "Twin Peaks"; opery mydlane; epoka cyfrowa; nostalgia; "Dynasty"; soap operas; digital age